Extraction of bioactive compounds from sesame (Sesamum indicum L.) defatted seeds using water and ethanol under sub-critical conditions. (15th December 2017) - Bodoira, Romina; Velez, Alexis; Andreatta, Alfonsina E.; Martínez, Marcela; Maestri, Damián
Highlights: Sesame bioactive compounds recovery was performed using water/ethanol at subcritical conditions. Theoretical models were run against experimental data in order to optimize extraction conditions. Lignans and phenolic compounds may be extracted simultaneously. Extracts obtained show similar antioxidant activity to that from synthetic antioxidants. Extraction time is markedly shorter than the usually used in conventional extraction processes. Abstract: Sesame seeds contain a vast array of lignans and phenolic compounds having important biological properties. An optimized method to obtain these seed components was designed by using water and ethanol at high pressure and temperature conditions. The maximum concentrations of lignans, total phenolics, flavonoids and flavonols compounds were achieved at 220 °C extraction temperature and 8 MPa pressure, using 63.5% ethanol as co-solvent. Under these conditions, the obtained sesame extracts gave the best radical scavenging capacity. Kinetic studies showed a high extraction rate of phenolic compounds until the first 50 min of extraction, and it was in parallel with the highest scavenging capacity. The comparison of our results with those obtained under conventional extraction conditions (normal pressure, ambient temperature) suggests that recovery of sesame bioactive compounds may be markedly enhanced using water/ethanol mixtures at sub-critical conditions.